2016
DOI: 10.3390/ijms17111899
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses Cyclin D1 Expression through Proteasomal Degradation in Human Hepatoma Cells

Abstract: The aim of this study is to explore the underlying mechanism on berberine-induced Cyclin D1 degradation in human hepatic carcinoma. We observed that berberine could suppress both in vitro and in vivo expression of Cyclin D1 in hepatoma cells. Berberine exhibits dose- and time-dependent inhibition on Cyclin D1 expression in human hepatoma cell HepG2. Berberine increases the phosphorylation of Cyclin D1 at Thr286 site and potentiates Cyclin D1 nuclear export to cytoplasm for proteasomal degradation. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Berberine promotes the phosphorylation of cyclin D1 at the T286 site and then accelerates binding of β-TrCP to cyclin D1 thus mediating its degradation. It was thus apparent that knockdown of β-TrCP expression could reduce this phenomenon (81). On the other hand, Nrf2 is a newly identified substrate of β-TrCP (82).…”
Section: Other F-box Proteins Involved In Chemoresistancementioning
confidence: 99%
“…Berberine promotes the phosphorylation of cyclin D1 at the T286 site and then accelerates binding of β-TrCP to cyclin D1 thus mediating its degradation. It was thus apparent that knockdown of β-TrCP expression could reduce this phenomenon (81). On the other hand, Nrf2 is a newly identified substrate of β-TrCP (82).…”
Section: Other F-box Proteins Involved In Chemoresistancementioning
confidence: 99%
“…Also, cyclin D1 overexpression is mainly responsible for tumor expansion, metastasis as well as angiogenesis. Berberine was found to repress the expression of cyclin D1 via proteasomal degradation in HCC [11]. In addition, our group identified that berberine exerted antimigratory and anti-invasive abilities in HCC cells involving the upregulation of PAI-1 and downregulation of uPA [12].…”
Section: Single Compounds From Chinese Medicine For the Treatment Of mentioning
confidence: 85%
“…19,20 Studies showed that BBR regulated cell cycle and inhibited cell proliferation in multiple cancers. 6,21,22 BBR induced G1 phase cycle arrest in A549 lung cancer cells through inhibition of the expression of Cyclin D1 and Cyclin E1. 21 In addition, a combination of an Hsp90 inhibitor and BBR inhibited cell growth via inhibition of CDK4 expression and modulation of cyclin D1 in colorectal cancer cells.…”
Section: Bbr Inhibits Cell Proliferation Bbr Regulates Cell Cyclementioning
confidence: 94%
“…22 In HepG2 human hepatoma cells, BBR suppressed cyclin D1 expression in vitro and in vivo. 6 Furthermore, BBR arrested the cell cycle at G1 via reduced expression of cyclin B1 and indirect inhibition of CDC2 kinase in several cancer cells. 23 In HBT-94 chondrosarcoma cells, BBR upregulated the expression of p53 and p21 by modulating activation of the PI3K/Akt and p38 signaling pathways, which resulted in G2/M phase arrest.…”
Section: Bbr Inhibits Cell Proliferation Bbr Regulates Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation